(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
The article presents the evaluation a building technical survey of a damaged historic rectory building in Luby near Cheb, it analyses the damage and proposes conceptual ideas for the rehabilitation design of a historic building damaged by the effects of natural seismicity applying the results and outputs of the NAKI II research project.